Development of an antigen-ELISA and a colloidal gold–based immunochromatographic strip based on monoclonal antibodies for detection of avian influenza A(H5) viruses. (September 2021) - Xiao, Yixin; Yang, Fan; Liu, Fumin; Cheng, Linfang; Yao, Hangping; Wu, Nanping; Wu, Haibo
Avian influenza A(H5) viruses (avian IAVs) pose a major threat to the economy and public health. We developed an antigen-ELISA (ag-ELISA) and a colloidal gold–based immunochromatographic strip for the rapid detection of avian A(H5) viruses. Both detection methods displayed no cross-reactivity with other viruses (e.g., other avian IAVs, infectious bursal disease virus, Newcastle disease virus, infectious bronchitis virus, avian paramyxovirus). The ag-ELISA was sensitive down to 0.5 hemagglutinin (HA) units/100 µL of avian A(H5) viruses and 7.5 ng/mL of purified H5 HA proteins. The immunochromatographic strip was sensitive down to 1 HA unit/100 µL of avian A(H5) viruses. Both detection methods exhibited good reproducibility with CVs < 10%. For 200 random poultry samples, the sensitivity and specificity of the ag-ELISA were 92.6% and 98.8%, respectively, and for test strips were 88.9% and 98.3%, respectively. Both detection methods displayed high specificity, sensitivity, and stability, making them suitable for rapid detection and field investigation of avian A(H5) viruses.